Analisis Hukum terhadap Pembiaran Penebangan Hutan dan Alih Fungsi Lahan Menjadi Perkebunan Sawit yang Memicu Banjir Bandang di Sumatera - Muhaiyaadden, Fadhil Ahda; Gunawan, Farhan; Jasmine Aulia, Naura; Imam Syahid, Muhammad; Munsif Ahmad, Adil (Adagium: Jurnal Ilmiah Hukum, 2026)
This study aims to conduct a legal analysis of the tolerance toward deforestation and land conversion into oil palm plantations that has triggered flash floods in Sumatra, as well as to examine the legal responsibilities of the government and corporations for the resulting ecological damage. The research addresses the contribution of deforestation to flash flood disasters, the legal provisions violated, and the mechanisms of legal accountability that may be applied. This research employs a normative legal method using statutory, conceptual, and analytical approaches, supported by secondary data derived from legislation, legal doctrines, scientific studies, and official environmental and forestry reports. The findings reveal that the tolerance of deforestation and the expansion of oil palm plantations have violated the Environmental Protection and Management Act, the Forestry Act, and the Plantation Act, and have significantly degraded the ecological function of forests as natural regulators of water systems. The impact of this research emphasizes that both governmental authorities and corporate actors may be held administratively, civilly, and criminally liable, and highlights the importance of environmental recovery efforts and sustainable prevention strategies to reduce the risk of future flash floods.